De-colonization, heritage, and advocacy : an Oxford handbook of applied ethnomusicology, volume 2 - Pettan, Svanibor, 1960-; Titon, Jeff Todd, 1943- (Oxford handbooks, 2019)
The nine ethnomusicologists who contributed to this volume present a diverse range of views, approaches, and methodologies that address indigenous peoples, immigrants, and marginalized communities. Discussing participatory action research, social justice, empowerment, and critical race theory in relation to ethnomusicology, De-Colonization, Heritage, and Advocacy is the second of three paperback volumes derived from the original Oxford Handbook of Applied Ethnomusicology. The Handbook can be understood as an applied ethnomusicology project: as a medium of getting to know the thoughts and experiences of global ethnomusicologists, of enriching general knowledge and understanding about ethnomusicologies and applied ethnomusicologies in various parts of the world, and of inspiring readers to put the accumulated knowledge, understanding, and skills into good use for the betterment of our world.